Characterization and comprehensive evaluation of phenotypic characters in wild Camellia oleifera germplasm for conservation and breeding - Chen, Tao; Liu, Li; Zhou, Yiling; Zheng, Qian; Luo, Siyuan; Xiang, Tingting; Zhou, Lijun; Feng, Shiling; Yang, Hongyu; Ding, Chunbang (Frontiers in Plant Science, 2023)
Camellia oleifera Abel. is an economically important woody oil plant native to China. To explore the genetic diversity of wild C. oleifera phenotypic traits and effectively protect these germplasm resources, this study provides a thorough evaluation of the phenotypic variability for a cluster of 143 wild C. oleifera germplasm resources. A total of 41 characters including leaves, flowers, fruits, seeds, and oil quality characters were investigated based on the quantization of physical, chemical descriptors and digital image analysis. The findings revealed significant variations among the 41 characters with high range of Shannon-Wiener indexes (H′) from 0.07 to 2.19. The coefficient of variation (CV) among 32 quantitative characters ranged from 5.34 to 81.31%, with an average of 27.14%. High genetic diversity was also detected among the 143 germplasm. Based on the analysis of hierarchical clustering, 143 accessions were separated into six categories. All the individuals can be clearly distinguished from each other according to the result of principal component analyses (PCA). The M TOPSIS exhaustive evaluation method based on correlation and PCA analyses of 32 quantitative characters was applied for the 143 wild C. oleifera accessions, and the top 10 varieties were identified as YA53, YA13, YA40, YA34, YA57, YA19, YA33, YA41, DZ8, and YA7. This research optimized the germplasm evaluation system and perfected the statistical phenotypic traits for DUS (Distinctness, Uniformity, Stability) testing. Some top-notch germplasm sources were also screened for Oil-tea Camellia breeding.